Efficiency of Several Cultural Methods and a Chick Bioassay to Recover Dry‐Stressed Campylobacter. Issue 1 (7th November 2014) - Cox, N.A.; Richardson, L.J.; Harrison, M.A.
Abstract C ampylobacter can become viable but nonculturable (VBNC) when environments are unfavorable. The VBNC state arises from exposure to sublethal adverse environmental conditions and recovery occurs by passage of the organism through a susceptible host. This study evaluated the efficacy of five enrichment procedures for recovery of dry‐atmospheric‐temperature stressed Campylobacter jejuni and Campylobacter coli and determined viability using a chick bioassay. Sterile chick paper pads and filter papers were inoculated at a low (L) and high (H) inoculum levels. Inoculated samples were left at room temperature and exposed to atmospheric conditions for up to 24 h with sampling performed periodically. Recovery rate decreased gradually from 0 to 2 h and then sharply from 2 to 4 h. For the chick bioassay, negative dry‐stressed samples at 6 and 24 h post inoculation were administered orally and intracloacally to day‐of‐age chicks. Seven days post inoculation, the chicks' ceca were analyzed for marker strains. This is the first study to use the intracloacal route of chicks to determine viability. Practical Applications The inability of conventional laboratory procedures to detect the presence of viable nonculturable Campylobacter from dry samples has led scientists to misunderstand the ecology of this microorganism in the integrated poultry industry. For example, when Campylobacter are not detected in dry hatchery samples (eggshell, fluff, chick pads), it is erroneously assumed that they are not present rather than not culturable. Breeder flocks and fertile eggs are indeed a source of Campylobacter to the young chick, but this has been overlooked and disregarded due to the nonculturable state of this microorganism. This study may convince poultry scientists to frequently question their lab results and may allow us to better understand the ecology of this elusive organism.